Rapture of the deep. - Weiss, G. (IEEE spectrum)
He makes the dive computer that every aquanaut wants. On one of the last shimmering days of summer, two weathered, middleaged men undress in a parking lot on the northeastern shore of Lake Zurich. This is the city's Gold Coast, where a halfway decent villa will set you back a couple of million francs. Jabbering in a Swiss dialect while working with swift, sure hands, the divers pull on thick black exposure suits and 20 kilograms of gear, including two big steel cylinders of pressurized breathing gas.